PERANCANGAN TUNGKU RE-HEATING PORTABLE - Ranggi Efnal Putra; Armila Armila; Rudi Kurniawan Arief (Rang Teknik Journal, 2023)
Re-heating furnace is a furnace that is used as a metal heater in the forging process. Re-heating furnace is one of the needs of the material technology laboratory to carry out the practical process of metal forming with plastic deformation as a heating medium for the forging process. The manufacture of this re-heating furnace is to make tools using medium carbon metal with a target temperature of 800℃. The process of making the furnace uses K300 type concrete material, 8mm reinforcing steel so that the furnace can be strong and durable. The furnace manufacture has succeeded in reaching a temperature of 302.8°C in 10 seconds using an air velocity of 15.4 km/h, and reaching a temperature of 931.8°C in 100 seconds using an air velocity of 25.7 km/h. This Re-heating Furnace can heat low-high carbon steel for forging process.